Calibration of mathematical water quality modeling in a river basin under critical conditions - Nakamura, Carolina Harue [UNESP]; Salla, Marcio Ricardo; Oliveira de Jesus, José Antônio; Ribeiro da Silva, Gustavo Henrique [UNESP] (Wiley, 2019)
In order to assist with the management of water resources, this study aimed to calibrate the water quality model “Ottocoded Critical Basins Analysis” (ABaCO) in a section of the Lambari River, located in the city of Poços de Caldas, Minas Gerais, Brazil, and it is considered qualitatively critical by the “National Water Agency” (ANA). The calibration results, obtained automatically by the Microsoft Excel® tool Solver, showed good adjustments between the simulated and observed concentrations for the following parameters: total nitrogen, organic phosphorus, inorganic phosphorus, and total phosphorus, considering a visual interpretation of the graphics. The other calibrated parameters (BOD, DO, organic nitrogen, ammoniacal nitrogen, and nitrate) obtained satisfactory adjustments. When evaluating the results by coefficient of determination, it was observed that all parameters showed negative values to one or more field campaigns. However, the calibrated values of the parameters can be incorporated into the model to obtain a first view of the river's qualitative situation, aiming to plan, control, and protect water resources to assist in decision-making and to favor performance of intervention analyses of environmental control measures. Practitioner points: Calibration of water quality model in a section of a river located in Brazil considered qualitatively critical; The calibration occurred automatically and manually, when it was necessary, in an Excel® spreadsheet, generated from the water quality model; The automation process was performed by the Excel® Solver tool through the objective function; Through visual interpretation, it was noticed that the calibrated parameters were well adjusted to the data observed in the field; Sensitivity analysis showed that the studied parameters did not show significant differences in relation to the values calibrated for parameters.
Keywords: calibration; Lambari River; water quality; water quality modeling